2018
DOI: 10.1016/s0140-6736(18)31572-1
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and cost-effectiveness of corticosteroid injection versus night splints for carpal tunnel syndrome (INSTINCTS trial): an open-label, parallel group, randomised controlled trial

Abstract: SummaryBackgroundTo our knowledge, the comparative effectiveness of commonly used conservative treatments for carpal tunnel syndrome has not been evaluated previously in primary care. We aimed to compare the clinical and cost-effectiveness of night splints with a corticosteroid injection with regards to reducing symptoms and improving hand function in patients with mild or moderate carpal tunnel syndrome.MethodsWe did this randomised, open-label, pragmatic trial in adults (≥18 years) with mild or moderate carp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
84
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 29 publications
5
84
0
7
Order By: Relevance
“…In recalcitrant cases, the physicians should consider surgical management, such as revision neuroplasty, neurolysis, and nerve reconstruction [12].Corticosteroids function as potent anti-inflammatory medications and have been widely used as the main injectate for treating CTS. A recent randomized controlled trial that recruited 234 patients with CTS demonstrated that a single corticosteroid injection was better than night splinting in terms of clinical effectiveness at six weeks post-injection [13]. The aforementioned result is consistent with that of a previous systematic review that revealed the short-term (at one month) benefits of corticosteroid injection in the treatment of CTS [14].…”
supporting
confidence: 85%
“…In recalcitrant cases, the physicians should consider surgical management, such as revision neuroplasty, neurolysis, and nerve reconstruction [12].Corticosteroids function as potent anti-inflammatory medications and have been widely used as the main injectate for treating CTS. A recent randomized controlled trial that recruited 234 patients with CTS demonstrated that a single corticosteroid injection was better than night splinting in terms of clinical effectiveness at six weeks post-injection [13]. The aforementioned result is consistent with that of a previous systematic review that revealed the short-term (at one month) benefits of corticosteroid injection in the treatment of CTS [14].…”
supporting
confidence: 85%
“…Corticosteroid injections have been found to be useful in both the diagnosis and treatment of CTS, with a benefit that has been supported by multiple systematic reviews and randomized controlled trials. [2][3][4][5] There is existing data showing that patients with less severe stages of CTS, as measured by median nerve cross-sectional area, swelling ratio, and symptom severity scores, are more likely to respond favorably to cortisone injections. 19 In addition to relieving symptoms of CTS in the short term, corticosteroid injections may also reduce the rate of surgery in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…For CTS, according to the guidelines for hand and wrist complaints, a corticosteroid injection is recommended as the first treatment step, which can be repeated after two to three weeks if complaints persist [37,39]. However, only 41% of the GPs recommended an injection as a first treatment step, and if complaints persisted, only 34% would repeat an injection.…”
Section: Discussionmentioning
confidence: 99%